PEMBUATAN SISTEM INFORMASI GEOGRAFIS PETA KEPENDUDUKAN, PEREKONOMIAN, PENDIDIKAN DAN KESEHATAN RAKYAT KOTA SURABAYA - Kurniawan, Gigih Aryo Septian (University of Surabaya, 2015)
Surabaya is one of the most populous city in Indonesia after Jakarta which have 31 sub-district and population around 3.123.914 people.Because of its population, Surabaya must improve its people welfare too.Badan Perencanaan Pembangunan Kota (Bapekko) Surabaya has a program which objective is to increase the quality of human resource of Surabayas citizen. One of the program is to held a human resource training for unemployed and poor citizen. The purpose of this program is to provide them knowledges on making marketable products so it can increase their welfare and create new jobs.Citizen who involved in this program is managed into one group called Kelompok Swadaya Masyarakat (KSM). Besides maintaining its citizen to get better welfare, Bapekko also provides annual report. This reports consists of various field, for example education, healthcare, population, and economy.Currently this report give information about condition of each sub-district. Unfortunately the report which made in form of table give a difficulty for searching information. Another problem is currently not having an information system for maintaining its program of human resource training, training management, ksm, and etc. According to this problem, an information system is needed to represent subdistrict information based on defined class, and adding a map feature to help present the real condition.This system also have feature of collectiing data and making reports for poor citizen who eligible to have training. This system is created by PHP, Google Maps API V3, and MySQL database. According to evaluation from few respondent from Bapekko, this system helps in createing a report for poor citizen data, training report, collecying poor citizen data, dan presting numerical data into map.